Novel Association of ABO Histo-Blood Group Antigen with Soluble ICAM-1: Results of a Genome-Wide Association Study of 6,578 Women: e1000118 - Paré, Guillaume; Chasman, Daniel I; Kellogg, Mark; Zee, Robert YL; Rifai, Nader; Badola, Sunita; Miletich, Joseph P; Ridker, Paul M (PLoS genetics, 2008)
While circulating levels of soluble Intercellular Adhesion Molecule 1 (sICAM-1) have been associated with diverse conditions including myocardial infarction, stroke, malaria, and diabetes, comprehensive analysis of the common genetic determinants of sICAM-1 is not available. In a genome-wide association study conducted among 6,578 participants in the Women's Genome Health Study, we find that three SNPs at the ICAM1 (19p13.2) locus (rs1799969, rs5498 and rs281437) are non-redundantly associated with plasma sICAM-1 concentrations at a genome-wide significance level (P<5×10-8), thus extending prior results from linkage and candidate gene studies. We also find that a single SNP (rs507666, P = 5.1×10-29) at the ABO (9q34.2) locus is highly correlated with sICAM-1 concentrations. The novel association at the ABO locus provides evidence for a previously unknown regulatory role of histo-blood group antigens in inflammatory adhesion processes.